New directions in Africa-China studies - Alden, Chris 1959-; Large, Daniel (Routledge, Taylor & Francis Group, 2019)
"Despite the accumulation of studies drawing from other fields, China-Africa studies still bears the hallmarks of its origins and popularization in IR - in Western and Chinese scholarship, and in this continues to shape subsequent work on it. New Directions in Africa-China Studies takes a step back from the 'events-driven' reactions and analysis characterizing much analysis in order to reflect more deeply on questions concerning how this has been, is and can be studied. This book offers a comprehensive and authoritative analytical review of the burgeoning area of China-Africa studies. The contributors draw on various disciplinary perspectives, posing not just methodological and theoretical questions about China-Africa and arguments for repositioning this as Africa-China but also raising wider issues, such as higher education in Africa or the global impact of China on social science. Showcasing a range of perspectives by an authoritative array of leading and emerging scholars, New Directions in Africa-China Studies is an essential read for scholars of the Africa-China relationships. It is also an authoritative resource for courses on African international relations, Chinese international relations, the South in Global Politics, or South-South development."...Publisher's summary
Includes bibliographical references and index
Keywords: Internationale Politik; Africa -- Relations -- China; China -- Relations -- Africa; China; Afrika; Aufsatzsammlung